Risk and Causes of Early Mortality among Extremely Preterm Infants Born Small for Gestational Age - Kehinde, Olasunkanmi; Tumin, Dmitry; Akpan, Uduak S.; Naylor, Martha (American Journal of Perinatology, 2025)
Extreme preterm (EPT) delivery, occurring before 28 weeks of gestation, carries high morbidity and mortality risks. Small for gestational age (SGA) infants, approximately 8 to 20% of EPT neonates, face increased risks. Mortality risk varies with gestational age and birth weight, with mixed reports on specific morbidities. This study aims to determine mortality rates and common causes of death among EPT SGA infants.The study used data from the CDC National Vital Statistics System, covering births and deaths from 2016 to 2021, with follow-up through 2022. It included infants born between 22 and 27 weeks gestation who were admitted to the neonatal intensive care unit. The outcome was all-cause in-hospital mortality within 30 days of birth, with causes of mortality classified based on the International Classification of Diseases, 10th revision codes. SGA was the primary independent variable.Based on a sample of n = 96,134 infants, we estimated 13% were born SGA and 30-day mortality rates were higher among SGA compared with non-SGA infants (31 vs. 13%). On multivariable analysis, SGA infants had higher 30-day mortality than non-SGA (odds ratio: 3.82; confidence interval 95% [CI]: 3.64, 4.01; p < 0.001), and were more likely to have death ascribed to complications of short gestation rather than other causes of death (relative risk ratio: 1.42; 95% CI: 1.27, 1.59; p < 0.001).SGA infants receiving intensive care have a high mortality risk, especially due to complications of short gestation and low birth weight complications.
Keywords: extreme prematurity; small for gestational age; causes of death; National Vital Statistics system